Mineração no município de Faina numa perspectiva da história ambiental - (1987-2015 ) - Morais, Jaqueline Pereira de (2020)
Mining process has been an important field to academic studies of environmental issues. To that end studies of interactions between the environment and society have claimed attention to Environmental History field, as is the case of our research. This study, entitled “Mining in the municipality of Faina in a perspective of Environmental History” covering the years 1987 to 2015. In that period artisanal mining and mining industry co-existed simultaneously in the municipality of Faina, Goias, Brazil. In the scope of Environmental History, this study aims to understand the array dimensions of the mining process since the colonial period in the municipality of Faina. Those dimensions are the perceptions and feelings of local residents about environment changes and also their positive or negative viewpoints from their experiences in life. Furthermore, this study seeks to link the mineral extraction process historic event to the population development of Faina along with understanding political implementations made by Sertão and Orinoco companies in the perspective of the environmental changes. The considerations presented supports the analysis of the respondents' responses to this historical process that they experienced. The data from this study suggest an economic problem in the municipal area, in addition, a high rate of unemployment. On the other hand, the data also shows the population from the municipality of Faina perceived the infrastructure improvements as a result of the mining process. Whereas, in fact, the improvements are made from the municipal government. This suggests naturalisation of mining in the Faina history as a consequence of the presence from this activity since the beginning formation of the municipality. In view of environmental issues, it has been observed a lack of knowledge about it. Few people could answer the questions. But when the questions were answered the responsibility for environmental matters were assigned to landowners only. This finding presents a significant influence of the advertising campaigns sponsored by companies and politicians in the opinions of local residents about environmental changes.